Multi-functional fluorescent carbon dots with antibacterial and gene delivery properties1. Issue 58 (25th June 2015) - Dou, Qingqing; Fang, Xiaotian; Jiang, Shan; Chee, Pei Lin; Lee, Tung-Chun; Loh, Xian Jun
<x xml:space="preserve">Abstract</x> Dual-functionality carbon dots with both anti-microbial and gene transfection abilities were developed and their properties elaborated in this paper.